Influence of cognitive interferences and self-talk functions on performance during competition in elite female field hockey players - Pérez-Encinas, C.; Fernández-Campos, F. J.; Rodas, G.; Barrios, C. (The Journal of Strength and Conditioning Research, 2016)
Cognitive interferences in the form of distracting thoughts and self-talk functions may play an important role in athletes' performance. The purpose of this study was to explore the types of interfering thoughts and the concomitant use of self-talk functions occurring in a sample of elite female field hockey players. The variation in these interferences in relation to athletes' performance level in competition was also investigated. Thirty-two female players of the first and the Under-21 National Team completed the Thought Occurrence Questionnaire for Sport and the Self-Talk Questionnaire after an international competition. The trainer rated the players' performance during competition in 3 different categories according to his expectancies based on the athletes' conditioning: Low (n = 6), Normal (n = 15), and High Performance (n = 11). Those players classified as low performing had increased the occurrence of irrelevant thoughts as compared with other groups. These athletes also showed the highest scores on the thoughts of escape subscale. Athletes with high performance during tournaments exhibited the lowest scores on all subscales, especially in thoughts of escape. The S-TQ subscales showed no differences among the 3 performance groups. Under-21 players had higher scores on the occurrence of performance worries and thoughts of escape subscales than first national team players. Interfering thoughts are common in female field hockey players during world-class competitions. The occurrence of irrelevant thoughts and thoughts of escape was related to players exhibiting low performance. The use of self-talk functions was relatively low in these athletes and could explain the enhanced occurrence of interfering thoughts